2013
DOI: 10.12968/ijpn.2013.19.10.510
|View full text |Cite
|
Sign up to set email alerts
|

General nurses' experiences of end-of-life care in the acute hospital setting: a literature review

Abstract: Approximately 90% of the UK population spend some time in hospital in their final year of life, and more than half of the population die in hospital. This review aims to explore the experiences of general nurses when providing end-of-life care to patients in the acute hospital setting. Nine studies were identified through a literature search, and each was then analysed and evaluated until themes emerged. Six themes were drawn from the literature: lack of education and knowledge, lack of time with patients, bar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 29 publications
2
60
1
Order By: Relevance
“…A recent meta-synthesis of the palliative care experience in hospital, based on patient and caregiver narratives from 16 studies, identified 6 essential themes, seemingly applicable to all care settings: expert care, effective communication and shared decision making, respectful and compassionate care, adequate environment for care, family involvement, and financial affairs (Virdun et al, 2016). These authors report that these specified priories have remained consistent over time-also reflecting continuing gaps in this care (Cardona-Morrell et al, 2016;McCourt et al, 2013;Pringle et al, 2015;Robinson et al, 2014). The findings of these studies and ours characterize the optimal type of care that needs to be available to dying patients, regardless of setting, and sets a standard for system development.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-synthesis of the palliative care experience in hospital, based on patient and caregiver narratives from 16 studies, identified 6 essential themes, seemingly applicable to all care settings: expert care, effective communication and shared decision making, respectful and compassionate care, adequate environment for care, family involvement, and financial affairs (Virdun et al, 2016). These authors report that these specified priories have remained consistent over time-also reflecting continuing gaps in this care (Cardona-Morrell et al, 2016;McCourt et al, 2013;Pringle et al, 2015;Robinson et al, 2014). The findings of these studies and ours characterize the optimal type of care that needs to be available to dying patients, regardless of setting, and sets a standard for system development.…”
Section: Discussionmentioning
confidence: 99%
“…The main goal of the literature review was to assess the current theoretical and scientific knowledge regarding the phenomenon of disaster health management in Saudi Arabia [14]. Through the literature review, the researcher was able synthesize the information and data already known, and then determine what is unknown.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The literature appears to be consistent in the view that terminally ill patients are best cared for in specialized care settings, such as palliative care units and hospices. However, increasing demands on health services will result in greater numbers of dying patients being admitted to the acute hospital settings [14]. The question posed then is, perhaps there is room for more options?…”
Section: How Golden Room Care Can Supplement To Hospice Carementioning
confidence: 99%